Antiangiogenic therapy exerts antitumor effects by altering the tumor microenvironment: bibliometric analysis - Kang, Yuan; Kang, Yixin; Zhang, Dianbao; Yao, Jun (Frontiers in Immunology, 2024)
BackgroundAntiangiogenic therapy can alter the tumor microenvironment (TME) and thus exert anti-tumor effects, and has the potential to increase the efficacy of conventional therapy and immunotherapy. The aim of this study was to examine current research hotspots and collaborative networks on the relationship between previous antiangiogenic therapies and the TME through bibliometric analysis.MethodFrom the Web of Science Core Collection database, all publications from inception through December 2023 were downloaded. In-depth analysis was performed by Bibliometrix packages in R. Keywords and collaborative networks were analyzed using VOSviewers and Citespace.ResultWe obtained a total of 9027 publications. They come from 27 countries and were published in 1387 journals, with a total of 39,604 authors in the studied area. The number of publications increases dramatically from 2014 to 2023, accounting for 73.87% (6668/9027) of all publications. China and CANCERS have the highest number of publications on this topic and CANCER RESEACH is the most influential. In the last decade (2013- 2023), research has gradually shifted from studying the role of vascular endothelial growth factor in the TME to examining how antivascular therapy can contribute to the progression of cancer treatment. Furthermore, nanoparticle-based drug delivery systems and immunotherapy have been widely explored in the past five years. The findings of this study will help scientists to explore this promising field in depth by providing insight into the relationship between antiangiogenic therapy and the TME.ConclusionThe relationship between the antiangiogenic therapy and the TME has been developing rapidly, but cooperation between different institutions and countries is still limited. Researchers can use this study to identify hotspots and develop trends for related research, thereby facilitating the development and cooperative exchange in this field, as well as to suggest potential future research directions.